New Keynesian microfoundations revisited: a Calvo-Taylor-rule-of-thumb model and optimal monetary policy delegation - Mash, R (University of Oxford, 2003)
We analyze the microfoundations of the Phillips curve and the close links between that relationship and results concerning optimal monetary policy, stabilisation bias and monetary policy delegation. Most recent literature has used a New Keynesian Phillips Curve based on Calvo pricing, often with an additional lagged inflation term motivated by rule-of-thumb behaviour. We develop a framework which encompasses this workhorse model while allowing for a richer time dependent pricing rule. This permits a more general analysis while showing that the standard model and policy conclusions derived from it are not robust to relatively minor changes in its microfoundations.